Pengaruh Sales Promotion, Perceived Quality, Dan Lifestyle Terhadap Repurchase Intention Pada Produk Outdoor Brand Eiger - Dewi, Fitana; Kartomo, Kartomo; Stiadi, Muhamad (Jurnal Mirai Management, 2024)
This research aims to determine: The influence of Sales Promotion, Perceived Quality, and Lifestyle on Repurchase Intention for Outdoor Brand Eiger products. This research is research with a quantitative approach. Data collection through distributing questionnaires using Google Form. The population in this study were all users of Outdoor Brand Eiger products in Kolaka Regency. Determination of sample size using the Hair formula (2014) namely 102 people by multiplying the number of indicators by a minimum value of 5-10. Testing research instruments uses validity tests and reliability tests. This research uses the Multiple Linear Regression Analysis method with data processing using the SPSS 25.0 application, the calculation results show that Sales Promotion has a positive and significant effect on Repurchase Intention (Sig.0.009 < 0.05), Perceived Quality has a positive and significant effect on Repurchase Intention (Sig. 0.000 < 0.05), and Lifestyle has a positive and significant effect on Repurchase Intention (Sig. 0.000 < 0.05). Apart from that, this research also shows that Sales Promotion, Perceived Quality and Lifestyle simultaneously also have a positive and significant effect on Repurchase Intention (Sig. 0.000 < 0.05). Keyword: Sales Promotion, Perceived Quality, Lifestyle, and Repurchase Intention